Calico Joe - Grisham, John. (New York : Doubleday, 2012)
In this novel, the careers of a golden boy rookie hitter for the Cubs and a hard-hitting Mets pitcher take very different paths. The baseball is thrilling, but it is what happens off the field that makes this story a classic.
Keywords: Baseball stories; Baseball players -- Fiction